2006
DOI: 10.1021/ja0626685
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Nuclear Polarization of Amyloidogenic Peptide Nanocrystals:  GNNQQNY, a Core Segment of the Yeast Prion Protein Sup35p

Abstract: Dynamic nuclear polarization (DNP) permits a approximately 10(2)-10(3) enhancement of the nuclear spin polarization and therefore increases sensitivity in nuclear magnetic resonance (NMR) experiments. Here, we demonstrate the efficient transfer of DNP-enhanced (1)H polarization from an aqueous, radical-containing solvent matrix into peptide crystals via (1)H-(1)H spin diffusion across the matrix-crystal interface. The samples consist of nanocrystals of the amyloid-forming peptide GNNQQNY(7-13), derived from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
334
2
9

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 266 publications
(357 citation statements)
references
References 44 publications
12
334
2
9
Order By: Relevance
“…In a study performed on 100-200 nm thick GNNQQNY peptide crystals by van der Wel et al, 59 only a slight decrease (B25%) in the proton DNP enhancement was observed when the enhancement of the radical containing solvent and the isolated protein enhancements were compared. The solvent signals show the maximum proton enhancement since the radical polarizes this part first.…”
Section: Estimation Of Dnp Penetration Depthmentioning
confidence: 91%
“…In a study performed on 100-200 nm thick GNNQQNY peptide crystals by van der Wel et al, 59 only a slight decrease (B25%) in the proton DNP enhancement was observed when the enhancement of the radical containing solvent and the isolated protein enhancements were compared. The solvent signals show the maximum proton enhancement since the radical polarizes this part first.…”
Section: Estimation Of Dnp Penetration Depthmentioning
confidence: 91%
“…Two research areas in which high resolution MAS experiments have proved especially successful are studies of amyloid fibrils [37,[51][52][53][54][55][56][57] and membrane proteins [42,[58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75]. However, in both of these cases, low sensitivity currently limits the information that can be gleaned from the spectra.…”
Section: Dnp Experiments On the Membrane Protein Bacteriorhodopsinmentioning
confidence: 99%
“…However, in both of these cases, low sensitivity currently limits the information that can be gleaned from the spectra. Accordingly, we recently demonstrated the use of DNP to enhance signal intensities in MAS spectra of amyloidiogenic nanocrystals [37] and we are currently utilizing DNP to improve the sensitivity of MAS spectra of the membrane protein bacteriorhodopsin (bR) [42,76,77]. In order to motivate the reader's interest in DNP, we devote this section to illustrating some of the scientific experiments that are possible with the increased sensitivity that is currently available, and the applicability of the DNP technique to scientific questions involving membrane proteins.…”
Section: Dnp Experiments On the Membrane Protein Bacteriorhodopsinmentioning
confidence: 99%
See 2 more Smart Citations